Menjangkau Sasaran melalui Sosial Media: Inovasi Edukasi Kesehatan Masyarakat di Era Pandemik Covid-19 - Supriyati Supriyati; Nindi Deshira Putri; Kevin Darmawan; Riski Suaidah; Pramudhita Yudhistira; Ahmad Kevin Ismandhani; Endah Amalia Permatasari (Jurnal Pengabdian dan Pengembangan Masyarakat, 2022)
Globally, health literacy on the Covid-19 is poor and underestimated. The intensive health education will improve the health literacy on the Covid-19 and important to control and prevent the Covid-19. The health protocol suggest that everyone should apply the physical distancing. Thus, the health education through social media was applied to reach the target audiences for improving the health literacy on the Covid-19. Instagram was chosen as the communication chanell for the program that targeted to youth. This program had been done in March 2020 which targeted to the Indonesian youth people who access internet and Instagram. The health message was developed based on the newest version of the Covid-19 control guidance that issued by the Ministry of Health Republic Indonesia. There were more than 3.500 people viewed the message on the Instagram, and part of them gave positive response and tried to send the message forward to their social network. This program indicated that Instagram was became the alternative communication channel to increase health literacy on the Covid-19, especially for youth.